Diversidade de leptoceroidea (insecta: trichoptera) no nordeste do Pará: novos registros e uma nova espécie - FURTADO, Laisse Moura (2022)
The insect order Trichoptera contains approximately 16,000 described species and has a high dependance of freshwater environments, since its immature stages inhabit streams, rivers, lakes and pools and the adults are winged and terrestrial. The caddisfly order is divided into 63 families and six of them: Leptoceridae, Mollanidae, Atriplectididae, Calamoceratidae, Philorheithridae and Odontoceridae form the superfamily Leptoceroidea, in the suborder Integripalpia, which gathers most of the caddisfly species diversity. Despite recent advances on the knowledge of Trichoptera in Neotropical region, there are gaps to be filled, especially in critically endangered biomes, such as the Amazon rainforest, which has its biggest area in Northern Brazil. In this region, Pará state presents a profitable scenario that might harbour many unknown species and new records, given its varied environments (e.g. mangrove, rainforest, swamps) and the scarcity of taxonomic studies developed in the area. This study contributes on the knowledge of Leptoceroidea diversity in Pará State through collection and identification of biological specimens of caddisflies in the state northeastern region (Bragança, Santa Luzia do Pará and Viseu municipalities). In this study, ten species of Leptoceroidea are recored for the first time in the State: Marilia alata, Nectopsyche muhni, Nectopsyche multilineata, Oecetis bidigitata, Oecetis cassicoleata, Oecetis doesburgi, Oecetis iguazu, Phylloicus auratus, Phylloicus fenestratus and Triplectides maranhensis; Oecetis bidigitata was previously known from Bolivia Only. Also, we describe and illustrate a new species of Oecetis (Trichoptera: Leptoceridae), which belong to Oecetis-testacea species group. The new species is diagnosed by its long phallic spine, apically curved, and inferior appendage with broad and rounded distal lobe with rounded apex; and small and discrete dorsal lobe, with truncate apex. This study increases from 10 to 20 the number of known species of Leptoceroidea in Pará State.